Comparison of the Effectiveness of Schema Therapy and Mindfulness on Sexual Infidelity and Marital Burnout - Agha Tehrani , Nayyereh; Bahreinian, Seyed Abdolmajid; Shahabizadeh , Fatemeh (Mental Health and Lifestyle Journal, 2024)
The present study aimed to compare the effectiveness of schema therapy and mindfulness-based intervention on reducing sexual infidelity and marital burnout among couples seeking psychological counseling. This quasi-experimental study employed a pretest–posttest control group design with a two-month follow-up. The statistical population consisted of 276 clients attending counseling centers in Isfahan in 2021, from which 45 participants were selected using Cohen’s sampling table and randomly assigned to schema therapy, mindfulness intervention, and control groups. The schema therapy program included eight 90-minute group sessions, while the mindfulness intervention consisted of nine 80-minute group sessions. Data were collected using the Marital Burnout Questionnaire and the Sexual Infidelity Questionnaire at three stages: pretest, posttest, and follow-up. Repeated-measures analysis of covariance and Bonferroni post-hoc tests were applied using SPSS-22. Repeated-measures ANCOVA revealed significant group effects for both sexual infidelity and marital burnout at posttest and follow-up (p < .001), with large effect sizes. Bonferroni comparisons indicated that both schema therapy and mindfulness interventions produced significantly greater reductions in sexual infidelity and marital burnout than the control group (p < .001), while no significant difference was observed between the two experimental groups (p = 1.000), indicating comparable therapeutic effectiveness. Both schema therapy and mindfulness-based intervention were found to be equally effective in significantly reducing sexual infidelity tendencies and marital burnout, and these improvements were maintained over time, supporting the use of either approach as a viable evidence-based intervention for enhancing marital functioning.